Immediate effects of photobiomodulation with low-level laser in women with no laryngeal or voice changes: preliminary results - Viviane Souza Bicalho Bacelete; Elisa Meiti Ribeiro Lin Plec; Flávio Barbosa Nunes; Andréa Rodrigues Motta; Ana Cristina Côrtes Gama (CoDAS)
ABSTRACT Purpose To assess the safety and immediate effect of photobiomodulation of low-level laser in vocally healthy women. Methods Experimental research in 36 vocally healthy women aged 18 to 45 years, with skin phototype I to III and body mass index below 25. Participants were randomized to form four groups: Group 1: placebo laser photobiomodulation followed by voiced tongue trill technique (VTTT); Group 2: 3 J infrared laser per point (total 21 J) followed by VTTT; Group: 3: 6 J infrared laser per point (total 42 J) followed by VTTT; and Group 4: 9 J infrared laser per point (total 63 J) followed by VTTT. The following outcomes were assessed: auditory-perceptual evaluation, acoustic analysis (jitter, shimmer, amplitude perturbation quotient [APQ], noise-to-harmonic ratio, period perturbation quotient, cepstral peak prominence, and cepstral peak prominence smoothed), and self-perceived phonatory effort. All participants’ records were taken before and immediately after the experiments. Results There was no significant difference in voice quality, acoustic parameters, or self-perceived phonatory discomfort between intervention moments in the placebo, VTTT + 3 J, and VTTT + 6 J groups in the intragroup comparison. G4 (VTTT + 9 J) decreased shimmer and APQ aperiodicity measures (respective p-values: 0.033; 0.044). Conclusion Results indicate aperiodicity measures improved with VTTT preceded by 9 J low-level laser application per point, commending this irradiation dosimetry as a possible energy for voice therapy in light-skinned and normal-BMI women. There was no evidence of worsened measures or in-creased discomfort with this resource, indicating it is safe for clinical practice.